Association of a Mutation in LACC1 With a Monogenic Form of Systemic Juvenile Idiopathic Arthritis. Issue 1 (January 2015) - Wakil, Salma M.; Monies, Dorota M.; Abouelhoda, Mohamed; Al‐Tassan, Nada; Al‐Dusery, Haya; Naim, Ewa A.; Al‐Younes, Banan; Shinwari, Jameela; Al‐Mohanna, Futwan A.; Meyer, Brian F.; Al‐Mayouf, Sulaiman
<x xml:space="preserve">Abstract</x> Objective The pathologic basis of systemic juvenile idiopathic arthritis (JIA) is a subject of some controversy, with evidence for both autoimmune and autoinflammatory etiologies. Several monogenic autoinflammatory disorders have been described, but thus far, systemic JIA has only been attributed to a mutation of MEFV in rare cases and has been weakly associated with the HLA class II locus. This study was undertaken to identify the cause of an autosomal‐recessive form of systemic JIA. Methods We studied 13 patients with systemic JIA from 5 consanguineous families, all from the southern region of Saudi Arabia. We used linkage analysis, homozygosity mapping, and whole‐exome sequencing to identify the disease‐associated gene and mutation. Results Linkage analysis localized systemic JIA to a region on chromosome 13 with a maximum logarithm of odds score of 11.33, representing the strongest linkage identified to date for this disorder. Homozygosity mapping reduced the critical interval to a 1.02‐Mb region defined proximally by rs9533338 and distally by rs9595049. Whole‐exome sequencing identified a homoallelic missense mutation in LACC1, which encodes the enzyme laccase (multicopper oxidoreductase) domain–containing 1. The mutation was confirmed by Sanger sequencing and segregated with disease in all 5 families based on an autosomal‐recessive pattern of inheritance and complete penetrance. Conclusion Our findings provide strong genetic evidence of an association of a mutation in LACC1 with systemic JIA in the families studied. Association of LACC1 with Crohn's disease and leprosy has been reported and justifies investigation of its role in autoinflammatory disorders.